2004
DOI: 10.1080/02841850410005615
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of new compression fractures in adjacent vertebrae after percutaneous vertebroplasty

Abstract: Thoracolumbar junction, shorter distance from the treated vertebrae, and greater degree of height restoration of the cemented vertebrae may increase the fracture risk of vertebrae adjacent to cement vertebrae after vertebroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(72 citation statements)
references
References 15 publications
4
64
1
3
Order By: Relevance
“…A lordotic force carries the risk of unsuspected damage to the adjacent vertebral pedicle and facet joints. The risk of latent complications, such as cement leakage and pulmonary embolism, may increase with increasing number of treated vertebra [24,25]. In the present study, computed-tomography showed no injury to the adjacent vertebral structures after LP on the postoperative scan.…”
Section: Discussionsupporting
confidence: 53%
“…A lordotic force carries the risk of unsuspected damage to the adjacent vertebral pedicle and facet joints. The risk of latent complications, such as cement leakage and pulmonary embolism, may increase with increasing number of treated vertebra [24,25]. In the present study, computed-tomography showed no injury to the adjacent vertebral structures after LP on the postoperative scan.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, increased anterior vertebral height restoration is one of the well-known risk factor of VCFs. In particular, it increases the risk of the newly formed VCFs because of the restoration of vertebral height, and greater loading of adjacent vertebra16). Although this study did not showe significant differences between the no fractures group and adjacent fractures group, the fracture can increase due to the dynamic hammer effect in the same mechanism with cement intradiscal leakage, since the anterior vertebral restoration affect the development of remote segmental fractures in the comparison with nonadjacent fractures group.…”
Section: Discussionmentioning
confidence: 52%
“…The causes of new-onset fractures after vertebroplasty are still debated : progression of the underlying disease3,20,21), augmentation of implanted cements, increased physical activity11,16,18,27) are possible contributors. The pertinent question regarding new-onset fractures after vertebroplasty is whether the next fracture level could be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have concluded that the outcome was mainly due to procedure-related complications such as cement leakage or adjacent vertebral fracture, without considering pre-operative factors. 27,28 Other studies that identified pre-operative prognostic factors only focused on the post-operative pain improvement within the vertebroplasty group without comparison with the conservative group. 29-31 Conservative treatment including a rigid brace and painkillers is still the treatment of choice in OVCFs.…”
Section: Discussionmentioning
confidence: 99%